2018
DOI: 10.1155/2018/4089459
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ICOSL New Antigen Receptor Domains Inhibit T Cell Proliferation and Reduce the Development of Inflammation in the Collagen-Induced Mouse Model of Rheumatoid Arthritis

Abstract: Lymphocyte costimulation plays a central role in immunology, inflammation, and immunotherapy. The inducible T cell costimulator (ICOS) is expressed on T cells following peptide: MHC engagement with CD28 costimulation. The interaction of ICOS with its sole ligand, the inducible T cell costimulatory ligand (ICOSL; also known as B7-related protein-1), triggers a number of key activities of T cells including differentiation and cytokine production. Suppression of T cell activation can be achieved by blocking this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…This may be the mechanism by which Aire affects the pathogenesis of RA, but this conclusion needs to be veri ed by further in-depth studies. Research in a collagen-induced mouse model of rheumatoid arthritis showed that an anti-ICOSL antibody blocked the ICOS/ICOSL interaction, inhibited T cell proliferation, decreased joint in ammation and delayed and reduced overall disease progression and severity [34,35] ; these results suggested that ICOSL played an important role in the pathogenesis of rheumatoid arthritis, which was consistent with our research results, but the authors did not elucidate whether ICOSL affects the differentiation of Tfh cells. A recent study demonstrated that ICOS expressed by Tfh cells could affect AKT phosphorylation and mTORC1 activation through PDK1, thereby affecting the differentiation of Tfh cells [36] .…”
Section: Discussionsupporting
confidence: 78%
“…This may be the mechanism by which Aire affects the pathogenesis of RA, but this conclusion needs to be veri ed by further in-depth studies. Research in a collagen-induced mouse model of rheumatoid arthritis showed that an anti-ICOSL antibody blocked the ICOS/ICOSL interaction, inhibited T cell proliferation, decreased joint in ammation and delayed and reduced overall disease progression and severity [34,35] ; these results suggested that ICOSL played an important role in the pathogenesis of rheumatoid arthritis, which was consistent with our research results, but the authors did not elucidate whether ICOSL affects the differentiation of Tfh cells. A recent study demonstrated that ICOS expressed by Tfh cells could affect AKT phosphorylation and mTORC1 activation through PDK1, thereby affecting the differentiation of Tfh cells [36] .…”
Section: Discussionsupporting
confidence: 78%
“…Limitations of our study include the absence of a nonbinding VNAR-Fc isotype control and the small size of each treatment cohort. VNAR isotype control 2V has been extensively assessed in numerous in vitro cellular and non-cell based assays, and more importantly in in vivo pharmacokinetic and disease model studies across the mouse, rat, rabbit, and nonhuman primate model systems with no evidence to suggest any off-site target binding or pharmacologic effect 4042,68. These data in conjunction with efficacy data from prior in vitro and animal studies using the S17-Fc and A5-Fc VNARs informed our decision to use the minimum number of animals that would be sufficient to identify a significant effect on the control of ocular inflammation in the EAU model.…”
Section: Discussionmentioning
confidence: 99%
“…S17-Fc and A5-Fc were expressed transiently in human embryonic kidney 283 cells. VNAR-Fc proteins were purified using Protein-A affinity chromatography and protein functionality was confirmed by target specific binding and neutralization assays 4042. VNARs S17-Fc (20 mg/kg), A5-Fc (20 mg/kg), or PBS were administered by intraperitoneal (IP) injection on days 8, 10, and 12.…”
Section: Methodsmentioning
confidence: 99%
“…Stimulation of Tregs by ICOS‐L promotes Treg induction and stability 26 . General blockade of the ICOS‐L/ICOS costimulatory axis is of immunosuppressive character in vivo as blocking ICOS‐L reduces the severity of symptoms in G6PI‐induced arthritis 27 or collagen‐induced arthritis 28 resulting in inhibited Th effector responses 29 . However, the lack of ICOS signalling specifically in Tregs worsens the symptoms of diabetes and releases the suppression of IBD 24,30 …”
Section: Introductionmentioning
confidence: 99%